Clinical and neurocognitive outcome in symptomatic isovaleric acidemia - Grünert, Sarah; Lindner, Martin; Leichsenring, Michael (Orphanet journal of rare diseases, 2012)
Despite its first description over 40 years ago, knowledge of the clinical course of isovaleric acidemia (IVA), a disorder predisposing to severe acidotic episodes during catabolic stress, is still anecdotal. We aimed to investigate the phenotypic presentation and factors determining the neurological and neurocognitive outcomes of patients diagnosed with IVA following clinical manifestation.